2022
DOI: 10.2478/eko-2022-0006
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Variation in Pollinators’ Visitation of Lantana camara in a Tropical Urban Landscape: Does Butterfly Abundance and Richness Drive the Fruit Set?

Abstract: Pollinator richness, abundance and visitation frequency may be affected by the abundance of floral resources and abiotic factors, influencing plant reproductive success. We analysed whether the diversity, abundance and frequency of butterfly visitation on Lantana camara vary across the year in a tropical urban landscape and whether this variation in butterfly community influences plant’s reproductive success. A two-period survey, referred to here as rainier and drier seasons, was carried out in 12 spatially in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 44 publications
1
1
0
Order By: Relevance
“…In the Amazon, the rainfall regime interferes with the richness of butterflies. The pattern found in other studies shows more species in the period of dry season (oliveiRa et al 2021;cézaR et al 2022). Our study was developed mostly in the rainy season, although we found increasing results, the number of species would probably be higher if the observations were extended to the following months, into the dry season.…”
Section: Resultssupporting
confidence: 59%
“…In the Amazon, the rainfall regime interferes with the richness of butterflies. The pattern found in other studies shows more species in the period of dry season (oliveiRa et al 2021;cézaR et al 2022). Our study was developed mostly in the rainy season, although we found increasing results, the number of species would probably be higher if the observations were extended to the following months, into the dry season.…”
Section: Resultssupporting
confidence: 59%
“…However, due to the limited duration of our study, the conclusion regarding the functional specialization of halictid bees in C. lanceolata is preliminary. Previous studies in other plant species have shown that plant-pollinator interactions networks can exhibit temporal variation dynamics within and between flowering seasons (Traveset & Sáez 1997;Olesen et al 2008;Souza et al 2018;Cézar et al 2022). Therefore, further multi-year studies of C. lanceolata in its introduced range in Japan are necessary to assess the consistency and persistence of the observed plant-pollinator interactions.…”
Section: Floral Visitationmentioning
confidence: 98%
“…The authors found that despite the negative impacts of urbanization, tropical urban areas can support a diverse array of pollinator species. Cézar et al (2022) also highlighted the importance of considering changes in pollinator communities and their impact on fruit production, emphasizing that the relationship between pollinators and plants must be considered in conservation efforts. These findings demonstrate the need for an effective pollinator conservation plan that considers these multiple factors.…”
Section: Protecting Biodiversitymentioning
confidence: 99%